NODULAÇÃO DE RAÍZES DE FEIJOEIRO IRRIGADO, SOB INOCULAÇÃO DE SEMENTES E DOSES DE NITROGÊNIO. - FRANCO, jhonatan da silva; LOPES, Adriano da Silva; KRAESKI, Marcos Jefferson; MEDEIROS, Rosevaldo Domingos; SILVA, Davi Pessoa da (ANAIS DO ENIC, 2023)
-